Significance of phonology in Al-Raienee - Al Zahrani, Saeed bin Mohsen Salem (Journal of Humanities & Social Sciences, 2017)
In the name of God, the most gracious the most merciful, and peace be upon his noble messenger, his good family, companions and followers to the Day of Judgment. This research highlights the personality of the great scholar Imam Al Rucayni, who was sailing in a world of the worlds of language by identifying us his personality. The problem for this study lies in the absence of many researchers capable of differentiating between the letters ḍād and ẓā’, and also between other confusing letters, and in the explanation of confusion of many researchers of Arabic in that respect. The objective of this study of the manuscript departs from the separation between the letters ẓa and ḍād because the beauty of speech rests in its eloquence. Through the publication and recension of the book it is possible to know the methodology of Rucayni as a respectable linguistic personality. The author is not only restricted to phonetic aspect and the points of the two letters but he also mentioned several linguistic aspects in grammar, morphology and linguistic. As for the evidence, he takes Qur’anic verses and Hadith to show his religious tendency, and by relying on the opinions of linguists and some examples of poetry to support his proposition of different topics on linguistics. At the end of the manuscript he mentioned general rules in differentiating between the letters ẓa and ḍād. This study assumes descriptive methodology that relies on linguistic and historical recension for the author’s writing where this author of the manuscript introduced words containing the letter ẓa in poetry so as to help the audience understand the words and memorise the poetic verses. This study arrives at some conclusions the most important of which are Arabic language is distinguished with the letter ḍād, and also with the number of the words containing the letters ẓa and ḍād, and the words with both letters. This study points to the need for researchers interested in Arabic to know the difference between the two letters and to do a constant exercise to know the difference between the two letters and to memorise the related words.